Business Analytics and Sociomateriality: A Study on the Practice of Revenue Management in an Airline Company - Cavalcanti, Claudia Xavier (2020)
The aim of this article is to address the Business Analytics (BA) practice based on the sociomateriality approach within the Revenue Management (RM) context of an airline. The study proposes that BA is an active engagement process which is set between analysts and business managers according to their sociomaterial entanglement with analytical data and tools, which areused to generate new insights. The discussion is substantiated by the theoretical articulation of BA as applied to RM based on the sociomateriality approach, which acknowledges the synergetic interaction between human and material dimensions by keeping their distinction from intentionality. The empirical investigation followed a qualitative design supported by nonparticipatory observation, interview and document research, which were the data collection techniques. The collected data was analyzed through spiral analysis associated with a practices’ description and analyses framework. Results have supported the BA proposition by evidencing the human/material dimension entanglement to produce BA-practice specificities.